Itrax data of Holocene sediment sequence retrieved from Lake Loitsana, Finland - Shala, Shyhrete; Helmens, Karin; Engels, Stefan; Kuhry, Peter; Kylander, Malin E; Luoto, Tomi P; Salonen, Sakari; Väliranta, Minna; Weckström, Jan (PANGAEA, 2025)
This dataset provides Itrax data for the early Holocene part of the sediment sequence retrieved from Lake Loitsana (Finland) in 2008. Itrax values (counts per second) for selected elements are presented against both depth (cm) and age (cal yr. BP; Shala et al., 2014). Total number of counts per step, MSE (mean square error), coherent and incoherent scattering data is presented as well. The Itrax dataset was used to provide information on early Holocene landscape dynamics at lake Loitsana. Elemental peak areas in the sediment succession were analysed with the X-ray fluorescence (XRF) core scanner at the Department of Geological Sciences, Stockholm University. The cores were scanned using a molybdenum-tube at 2 mm resolution (voltage 30 kV, current 45 mA) and 30 s measuring time. The peak areas for each step have been normalised by the total number of counts (kcps) for that step, in order to remove various instrumental effects. The analyses were performed in the laboratories of Stockholm University, Sweden.
Keywords: Chironomids; C/N; diatoms; Finland; Holocene; Itrax; LOI; Macro-remains; Pollen; Sokli; Stable isotopes